Late strut fracture in a Björk-Shiley valve prosthesis (current series). - Sacks, S H (1984)
Fracture of the short strut of the latest series of Björk-Shiley mitral valve prostheses occurred 12 months after implantation. The patient died despite emergency surgery to excise and replace the prosthesis. Björk-Shiley 29-33 mm valves with a 60 degree opening angle manufactured between February 1981 and March 1982 have a predicted strut fracture rate of 0.3% (three times greater than that of valves produced outside these dates). Unimplanted valves from this batch have now been recalled by the manufacturers.